Some New Types of Orthogonalities in Normed Spaces and Application in Best Approximation - Ojha, Bhuwan Prasad (Journal of Advanced College of Engineering and Management, 2016)
In this paper, two new types of orthogonality from the generalized Carlssion orthogonality have been studied and some properties of orthogonality in Banach spaces are verified and as best implies Birkhoff orthogonality and Birkhoff orthogonality implies best approximation, in this paper, Pythagorean orthogonality also implies best approximation has been proved. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, page: 1-4